Overview of Personal Protective Equipment Use Among Oil Palm Farmers in Simpang Pematang Subdistrict, Mesuji Regency - Camilia, Anita; Saftarina, Fitria; Febriani, Wiwi; Larasati, TA (CV. Jasa Sukses Abadi, 2024)
The use of personal protective equipment (PPE) is an essential effort in preventing occupational health and safety risks, especially for farmers working in the plantation sector. This study aims to analyze the use of PPE among oil palm farmers in Simpang Pematang Subdistrict, Mesuji Regency. The research employs a cross-sectional approach involving 105 oil palm farmers selected through purposive sampling. Data were collected using questionnaires and analyzed univariately. The findings show that the level of compliance with PPE usage is still low, with only 48.6% of farmers consistently adhering to PPE usage procedures. The use of specific PPE items such as masks and protective glasses is particularly low, at just 13.3% and 5.7%, respectively. The main barriers to PPE use include farmers' lack of understanding about its importance, limited availability of PPE, and misconceptions about its comfort. This study concludes that strategic efforts are needed to improve PPE compliance through education, outreach programs, and the provision of adequate PPE.